Analysis of Decent and Fair Work for Precarious Workers in the Lombok Industrial Area - Rakhmat Nur Adhi; Jepri Utomo; Nursaptini Nursaptini; Lalu Muslihul A Akhmadi (Early Publishing, 2026)
Precarious employment is a critical issue in modern employment, including in the industrial areas of Lombok, West Nusa Tenggara (NTB). These workers, generally contract or outsourced workers, face job instability, low wages, and limited access to social security and health protection. This situation poses serious challenges to the implementation of decent work and fair work principles. This research employed a qualitative approach with a case study method. Informants were purposively selected, consisting of seven workers in the industrial areas of Lombok, including contract workers, outsourced workers, teachers, and company management. Data were collected through in-depth interviews, direct observation of work activities, and documentation in the form of notes, photographs, and recordings. The results show that precarious workers face significant limitations in terms of job stability, adequate wages, health and safety protection, and participation in decision-making. Short-term contract practices, the risk of termination of employment, and minimal union representation exacerbate their vulnerability. Structural factors such as high worker numbers and limited skills weaken their bargaining position. In conclusion, vulnerable workers in Lombok require more inclusive labor regulations, adequate social protection, and collective worker empowerment to create more stable, decent, and equitable working conditions. This research provides empirical insights and information for sustainable industrial development policies.